Annular size and interaction with trans-catheter aortic valves for treatment of severe bicuspid aortic valve stenosis: Insights from the BEAT registry. (15th February 2022) - Moscarella, Elisabetta; Mangieri, Antonio; Giannini, Francesco; Tchetchè, Didier; Kim, Won-Keun; Sinning, Jan-Malte; Landes, Uri; Kornowski, Ran; De Backer, Ole; Nickenig, Georg; De Biase, Chiara; Søndergaard, Lars; et al.
Abstract: Background: Transcatheter aortic valve replacement (TAVR) is safe and feasible in patients with bicuspid aortic valve (BAV), but whether annular size may influence TAVR results in BAV patients remains unclear. We aimed at evaluating the impact of aortic annular size on procedural and clinical outcomes of BAV patients undergoing TAVR, as well as potential interactions between annular dimension and trans-catheter heart valve (THV) type (balloon-expandable (BEV) vs. self-expanding (SEV). Methods: BEAT is a multicenter registry of consecutive BAV stenosis undergoing TAVR. For this sub-study patients were classified according to annular dimension in small-annulus (area < 400 mm 2 or perimeter <72 mm), medium-annulus (area ≥ 400 and < 575 mm 2, perimeter ≥72 mm and< 85 mm), large-annulus (area ≥ 575 mm 2 or perimeter ≥85 mm). Primary endpoint was Valve Academic Research Consortium-2 (VARC-2) device success. Results: 45(15.5%) patients had small, 132(45.3%) medium, and 114(39.2%) large annuli. Compared with other groups, patients with large annuli were more frequently male, younger, with higher body mass index, larger aortic valve area, higher rate of moderate-severe calcification, lower mean trans-aortic valve gradient and lower left ventricular ejection fraction. In large-annuli SEVs were associated with a lower VARC-2 device success (75.9% vs. 90.6%, p = 0.049) driven by a higher rate of paravalvular valvular leak (PVL) compared to BEVs (20.7% vs. 1.2%, p < 0.001). However, no differences in clinical outcomes were observed according to annular size nor THV type. Conclusions: TAVR in BAV patients is feasible irrespective of annular size. However in patients with large aortic annulus SEVs were associated with a significantly higher rate of PVLs compared to BEVs. Highlights: TAVR can be successfully performed in severe bicuspid aortic stenosis. However, interaction between annular size and THV type is still unclear. We compared BEV and SEV hemodynamics by aortic annulus size in BAV patients. In large annuli a higher rate of PVLs was observed SEVs compared to BEVs. No differences in clinical outcomes were observed according to annular size nor THV.